THE DEVELOPMENT DYNAMICS OF FOOTBALL AND ITS INFLUENCE ON CONSERVATISM CULTURE IN SAUDI ARABIA - Fauzul, Ardia Yunda; Imamuddin, Basuni (International Review of Humanities Studies, 2023)
This research discusses the development dynamics of Saudi Arabian football and its influence on conservatism culture in that country. Saudi Arabia is known as a conservative country and tends not to be inclusive toward outside cultures. However, in the past few years, Saudi Arabia has begun to open up and be moderate, including in the realm of sports. This research is interesting to discuss because football, which is actually the most popular sport in Saudi Arabia, has actually become a channel for creating a cultural transformation from conservative to moderate. This study aims to explain the history and development of Saudi Arabian football and its relation to the culture of conservatism that has been rooted in Saudi Arabia for a long time. This research is a descriptive qualitative research with library research method. The theory in this study refers to the theory of social change according to John Lewis Gillin and John Phillip Gillin. The results of the study show that football is a channel that capable to transforming Saudi Arabia's conservatism culture into a moderate culture through loosening of prevailing norms such as allowing women to watch football matches in stadiums, establishing women's competitions and national teams, and allowing cohabitation for foreign football player.